The chick and the duckling - Suteyev, Vladimir; Dewey, Ariane; Aruego, Jose.; Ginsburg, Mirra (New York Macmillan, 1972)
Hatched at the same time, the chick does fine imitating the duckling until the latter goes for a swim.
Keywords: Chickens -- Fiction; Ducks -- Fiction